2023
DOI: 10.21608/ijtah.2023.213676.1090
|View full text |Cite
|
Sign up to set email alerts
|

Customers’ behavioral intensions towards gas stations fast-food outlets in Egypt.

Abstract: With the Egyptians' changing lifestyle, especially working people and students are seeking easy access and rapid solutions. Gas stations convenience stores are continuing to grow and attract more customers. This study aims to determine how the general behavioral intentions of customers are influenced by characteristics present at fast-food outlets found in gas stations, such as the quality of the food, convenience, perceived service quality, and price.This study presents the results of a questionnaire survey c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…, 2022). At the same time, a response is provided to the recommendation of Kamel and Monsaur (2023) who suggested that the influence of PE on the CS of fast-food be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…, 2022). At the same time, a response is provided to the recommendation of Kamel and Monsaur (2023) who suggested that the influence of PE on the CS of fast-food be evaluated.…”
Section: Discussionmentioning
confidence: 99%